Case report on congenital syngnathia: Surgery and a 4-year follow-up - Parit Ladani; Niyati Satish Balse; Bhalchandra Jayakar; Hermann Sailer (Wolters Kluwer Medknow Publications, 2021)
Syngnathia is an extremely rare craniofacial malformation affecting the upper and lower jaws, in particular, and adjacent bony and soft tissues, to lesser or greater extent. Fusion of jaws leads to complications such as compromised airway and breathing, feeding difficulty, and poor growth. An early multidisciplinary intervention, surgery at the appropriate time, and meticulous postoperative monitoring are most imperative in its management. We describe a case of a 6-month-old child with congenital syngnathia that was managed successfully. Four-year follow-up revealed satisfactory outcomes and the need for corrective jaw surgeries after growth completion for improved function and esthetics. Anesthesia considerations, feeding, surgical management, postoperative care, and follow-up as well as growth regulation have been discussed in detail.